Correction: Enhanced photocatalytic activity of TiO2–Cu/C with regulation and matching of energy levels by carbon and copper for photoreduction of CO2 into CH4. Issue 6 (23rd January 2018) - Yan, Yabin; Yu, Yanlong; Cao, Chi; Huang, Shaolong; Yang, Yajun; Yang, Xiaodan; Cao, Yaan
Abstract : Correction for 'Enhanced photocatalytic activity of TiO2 –Cu/C with regulation and matching of energy levels by carbon and copper for photoreduction of CO2 into CH4 ' by Yabin Yan et al., CrystEngComm, 2016, 18, 2956–2964.